Parasitism of Zatypota riverai Gauld (Hymenoptera: Ichneumonidae: Pimplinae) on Anelosimus baeza Agnarsson (Araneae: Theridiidae) in northeast Brazil, with a description of the male - Sobczak, Jober Fernando; Messas, Yuri Fanchini; Pádua, Diego Galvão De (Zootaxa, 2017)
Ichneumonid wasps of the Polysphincta genus-group (Polysphinctini sensu Townes hereafter “polysphinctine wasps”) are exclusively koinobiont ectoparasitoids of spiders (Fitton et al. 1987; Gauld 2006). Since the first report of a spider’s behavior being manipulated by a polysphinctine wasp (Eberhard 2000), several studies have since focused on unravelling the mechanisms and evolution of this association (e.g. Gonzaga & Sobczak 2007; Matsumoto 2009; Sobczak et al. 2009; Eberhard 2010; Gonzaga & Sobczak 2011; Korenko & Pekár 2011; Korenko et al. 2013; Sobczak et al. 2014; Takasuka et al. 2015).